Unemployment and government : - Walters, William (Cambridge University Press, 2000)
This book follows the invention and transformation of unemployment, understood as a historically specific site of regulation. Taking key aspects of the history of unemployment in Britain as its focus, it argues that the ways in which authorities have defined and sought to manage the jobless have been remarkably varied. The book examines such institutionalized practices as the labor bureau, unemployment insurance, and the present "New Deal" as "technologies" of power. The result is a challenge to our thinking about welfare states.